A STUDY ON OSTEOPOROSIS AND IMPACT OF DRUGS & EXERCISE FOR ITS CLINICAL MANAGEMENT - Indra Kumar Dhoot; Yogesh Sharma (Journal of Biomedical and Pharmaceutical Research, 2020)
Aim: The purpose of study was “Prevention of an Osteoporosis by development of the intervention of education. To observe the severely affected bones due to rapid decline in BMD.Methods: all the data were collected after the patient counseling by the cross –sectional study in both sexes (n=163), aged 18 to 70 years, at CMHRC Hospital, Churu, India using random sample method. Individuals were classified as they having osteoporosis/ osteopenia characterized using T-Score after the DEXA scanning based on the WHO.Result: It was found that out of 58 patients 6, 24, 16 &12 patients of them were affected due to “wrong posture”, “Imbalanced diet, mineral & BMI” “Adverse drug reactions” & “Adverse effects of other associated disease”. Subjects with normal or lower BMI were more affected with osteopenia or initial stage of osteopenic fractures, when compared to overweight or obese patients. The sitting, sleeping & standing postures are to be altered while at work as they advance in age or in case of initial stage of osteopenic fractures. All the subjects are advised to follow the Posture related Education, Diet maintenance and required exercise to mimic the initial stage of osteopenia/osteoporosis and prevention of osteoporosis disorder. Significantly lower T-scores were observed at spine with (-) 2.05 ± 0.15 & hip bone with (-) 2.15 ± 1.25 respectively as compare to other bones either in men or women. That concludes that the susceptibility in the both spine and hip bone had rapid decline in the BMD instead of other bones.Keywords: BMD, T-score, Osteoporosis, Calcium supplements, skeletal disease, Osteopenia.